Chronic Omega-3 Polyunsaturated Fatty Acid Treatment Variably Affects Cellular Repolarization in a Healed Post-MI Arrhythmia Model - Bonilla, Ingrid M.; Nishijima, Yoshinori; Vargas-Pinto, Pedro; Baine, Stephen H.; Sridhar, Arun; Li, Chun; Billman, George E.; Carnes, Cynthia A. (Frontiers in Physiology, 2016)
Introduction: Over the last 40 years omega-3 polyunsaturated fatty acids (PUFAs) have been shown to be anti-arrhythmic or pro-arrhythmic depending on the method and duration of administration and model studied. We previously reported that omega-3 PUFAs do not confer anti-arrhythmic properties and are pro-arrhythmic in canine model of sudden cardiac death. Here we evaluated the effects of chronic omega-3 PUFA treatment in post- MI animals susceptible (VF+) or resistant (VF-) to ventricular tachyarrhythmias. Methods: Perforated patch clamp techniques were used to measure cardiomyocyte action potential durations at 50 and 90% repolarization and short term variability of repolarization. The early repolarizing transient outward potassium current Ito was also studied. Results Omega-3 PUFAs prolonged the action potential in VF- myocytes at both 50% and 90% repolarization. Short term variability of repolarization was increased in both untreated and treated VF- myocytes vs. controls. Ito was unaffected by omega-3 PUFA treatment. Omega-3 PUFA treatment attenuated the action potential prolongation in VF+ myocytes, but did not return repolarization to control values. Conclusions: Omega-3 PUFAs do not confer anti-arrhythmic properties in the setting of healed myocardial infarction in a canine model of sudden cardiac death. In canines previously resistant to ventricular fibrillation (VF-), omega-3 PUFA treatment prolonged the action potential in VF- myocytes and may contribute to pro-arrhythmic responses.